Elemental Sulfur‐Promoted [2+3+1] Annulation for Synthesis of Functionalized Thiochromeno[2, 3‐b]indoles from Indole Derivatives. Issue 6 (20th May 2020) - Liu, Jianming; Wang, Zhixian; Wang, Ke; Liu, Dong; Yang, Yan; Fan, Junjun; Zhuo, Kelei; Yue, Yuanyuan
Abstract: An intermolecular [2+3+1] annulation between indole and 2‐bromobenzylaldehyde derivatives was successfully achieved by utilizing elemental sulfur as the promoter and coupling partner. This direct and operationally simple procedure provided a rapid and reliable approach to synthesize functionalized thiochromeno[2, 3‐ b ]indoles. Preliminary mechanistic studies indicated that elemental sulfur enhanced the nucleophilicity of the 3‐position of indole to attack an aldehyde group, and C−H cleavage of indole was not involved in the rate‐determining step. Abstract : An intermolecular [2+3+1] annulation between indole and 2‐bromobenzylaldehyde derivatives was successfully achieved by utilizing elemental sulfur as the promoter and coupling partner. This direct and operationally simple procedure provided a rapid and reliable approach to synthesize functionalized thiochromeno[2, 3‐ b ]indoles.